Сутність та місце захисту інтелектуальної власності в системі економічної безпеки підприємства - Перевалова, Людмила Вікторівна; Окладна, Марина Георгіївна (НТУ "ХПІ", 2016)
У статті розглядаються проблеми захисту інтелектуальної власності на підприємствах у сучасних економічних умовах. На думку авторів, успішний розвиток підприємства, його високі фінансові результати залежать від впровадження у виробництво об’єктів інтелектуальної власності. Конкурентоздатність підприємства, у свою чергу, залежить від наявності надійного механізму захисту інтелектуальних ресурсів. Розкриваються такі поняття як «захист інтелектуальної власності», «економічна безпека підприємства», розглядається сутність інтелектуальної безпеки та економічної безпеки підприємства, місце, яке займає захист інтелектуальної власності в системі економічної безпеки підприємства. Автори аналізують зовнішні та внутрішні загрози, які можуть завдати шкоди діяльності підприємства. Розглянута система захисту інтелектуальної власності, запропоновані основні напрямки забезпечення захисту об’єктів інтелектуальної власності на підприємстві.

The article is devoted to the problems of intellectual property protection at the enterprises of Ukraine in the current economic environment. The successful development of the company and its high financial results depend on the implementation of intellectual property in production. The article reveals such concepts as "intellectual property protection", "enterprise economic security", considers the essence of enterprise intellectual and economic security, the place that protection of intellectual property takes in the system of enterprise economic security. The author analyzes the external and internal threats, which can damage the enterprise. The paper considers intellectual property protection system, proposes basic directions of enterprise intellectual property protection. One of the main conditions of enterprise intellectual property protection is its ability to withstand the threats that exist or may appear in the future. The authors allocate internal and external threats which can damage the enterprise. The article considers intellectual property protection system. The authors analyze main trends of enterprise intellectual property protection. In order to reduce internal threats, according to the author, it is necessary to amplify employees’ corporate spirit, implement mechanisms of their stimulation, increase discipline level and responsibility for enterprise rules violation. Employees’ activity should be protected and this is connected primarily to their career. The enterprise’s management should define the philosophy, the nature of management processes and corporate culture. All of this will ensure the effective intellectual property protection and, consequently, the effective enterprise development in modern conditions.
Essence and place of protection of intellectual property in the system of economic security of an enterprise
Keywords: право інтелектуальне; безпека економічна; загроза внутрішня; загроза зовнішня; safety; internal threats; external threats